Analysis of clinical phenotypes and genetic variations in two pedigrees affected with Weiss-Kruszka syndrome - Chunxiao Han; Changshui Chen; Yuxin Zhang; Haibo Li (BMC, 2024)
Abstract Background Weiss-Kruszka syndrome (WSKA) is a rare autosomal dominant syndrome characterized by multiple congenital anomalies caused by variants in the zinc finger protein 462 gene (ZNF462). About 40 cases of Weiss-Kruszka syndrome have been reported worldwide, and the aim of this study was to investigate the genetic causes of three patients from two Weiss-Kruszka syndrome family pedigrees with the aim of accumulating more data on the disease. Objective To explore the clinical and genetic characteristics of two pedigrees with Weiss-Kruszka syndrome. Methods The clinical data and family history of patients and family members of two pedigrees with Weiss-Kruszka syndrome were collected, and the pathogenic genes of the patients were analysed by whole-exon sequencing. Suspicious variants were verified by Sanger sequencing verification and bioinformatics prediction. Results Proband 1 has developmental delay, autistic behaviour, and abnormal electroencephalogram results. WES revealed a classical heterozygous c.6696-2 A > C splice variant of the ZNF462 gene, which was detected in neither parent. This position was conserved, and the variant was predicted to be deleterious. Minigene assays revealed that three types of aberrantly spliced mRNAs were produced. MRI of proband 2 suggested dysplasia of the corpus callosum with the formation of hemispheric cleft cysts, with a teardrop-like appearance in the lateral ventricle. WES revealed that a heterozygous c.4891 C > T:p. The Glu1631Ter nonsense variant of the ZNF462 gene was inherited from her mother. According to the guidelines of the American Society of Medical Genetics and combined with its clinical manifestations, c.6696-2 A > C and c.4891 C > T:p. Glu1631Ter was determined to be a possible pathogenic variant. Conclusion The c.6696-2 A>C and c.4891C > T:p.Glu1631Ter of the ZNF462 gene likely underlies Weiss-Kruszka syndrome in children (foetus), which enriches the variant spectrum of Chinese patients with Weiss-Kruszka syndrome and provides a basis for prenatal diagnosis and genetic counselling.